Left atrial volume index as a marker of left ventricular diastolic dysfunction in asymptomatic Tanzanian diabetic patients. (April 2013) - Chillo, Pilly; Rieck, Åshild E.; Lwakatare, Johnson; Lutale, Janet; Gerdts, Eva
Abstract Aim: To determine the prevalence of left atrial (LA) enlargement and its relation to left ventricular (LV) diastolic dysfunction among asymptomatic diabetic outpatients attending Muhimbili National Hospital in Dar es Salaam, Tanzania. Methods: Echocardiography was performed in 122 type 2 and 58 type 1 diabetic patients. Diastolic dysfunction was defined as peak transmitral blood velocity to medial mitral annulus velocity (E/E') ratio ≥ 15. LA volume indexed to body surface area (LAVI) was considered enlarged if ≥ 29 ml/m2. Results: Enlarged LAVI and LV diastolic dysfunction were more common in type 2 than in type 1 diabetic patients (44.3 vs 25.9% and 20.5 vs 3.5%, respectively, both p < 0.05). In multivariate linear regression analysis, larger LAVI was associated with LV diastolic dysfunction independent of significant associations with LV mass index and presence of mitral regurgitation in type 2 diabetic patients, while LV mass index, lower ejection fraction and longer duration of diabetes were the main covariates of larger LAVI in type 1 diabetic patients (all p < 0.05). Conclusion: Enlarged LA is common among asymptomatic Tanzanian diabetic patients, and particularly associated with LV diastolic dysfunction in type 2, and with cardiomyopathy and lower systolic function in type 1 diabetic patients.